EVOLUSI TEKNOLOGI LEPAS PANTAI KASUS INTERAKSI STRATEGIS DALAM INDUSTRI MINYAK: EVOLUTION OF OFFSHORE TECHNOLOGY A CASE OF STRATEGIC INTERACTION IN OIL INDUSTRY - Agustinus Denny Unggul Raharjo (JISTECH: Journal of Information Science and Technology, 2014)
Offshore operation in oil and gas industry defined as any drilling and production operation located or operating on a body of water, at some distance from the shore relatively to what identified as onshore operation which is generally means in land operation. Offshore drilling and production operation was a relatively new industry compare to the history of oil industry it self. Technologies take major part in development of offshore project, technologies make what impossible become possible in offshore industry. Offshore drilling and production industry can be possible because of technology innovation. However the drive to explore offshore resources come from high demand on oil and gas as well as depleted resources in onshore resources. One suggested that there is strategic interaction among entities in oil industry, as for offshore operation the strategic interaction lead to evolution of offshore technology. The strategic interaction between two relatively same profiles oil related company will depend on the cost of technology. There is tendency in oil and gas industry, if one company successful in using a kind of technology the other companies will follow the pad. Technology takes a big part in offshore drilling and production industry. The strategic interaction in offshore industry related to the cost of technology.